Disposable non-enzymatic impedimetric biosensor using Mn-doped ZnS-chitosan nanocomposite for tetracycline detection - Trong-Du Nguyen; Huy Quang Nguyen; Mai Thi Tran; Son Hai Nguyen; Cuong Danh Do (PLoS ONE, 2026)
Monitoring antibiotic residues in aquaculture water is critical for food safety, environmental protection, and antimicrobial stewardship. Here, we present a proof-of-concept disposable, non-enzymatic impedimetric biosensor for the rapid and selective detection of tetracycline. The sensor employs interdigitated electrodes functionalized with a manganese-doped zinc sulfide-chitosan nanocomposite, providing a stable, conductive, and environmentally friendly sensing interface. The successful synthesis of the nanocomposite was confirmed using scanning electron microscopy, high-resolution transmission electron microscopy, X-ray diffraction, energy-dispersive X-ray spectroscopy, and Fourier transform infrared spectroscopy. Using electrochemical impedance spectroscopy, the device exhibits a linear response over the range of 62.5–1000 nM tetracycline, with a limit of detection of 42 nM and a limit of quantification of 138 nM. It also displays strong selectivity over other common antibiotics, including ampicillin, amoxicillin, cephalexin, doxycycline, penicillin, and non-antibiotic interferent, glucose, as well as excellent reproducibility and operational stability under repeated measurements. The sensor can detect tetracycline in lake, tap, and bottled water with linear responses across the same concentration range. The combination of biocompatible, low-cost materials and simple fabrication supports single-use deployment and scalability. These results demonstrate the potential of manganese-doped zinc sulfide-chitosan nanocomposite-based impedimetric biosensors as practical platforms for on-site monitoring of antibiotic residues in aquaculture water.